Healthy lifestyle choices: new insights into vitiligo management - Liang, Xin; Guo, Fei; Fan, Qian; Cai, Xiaoce; Wang, Jiao; Chen, Jiale; Liu, Fang; Du, Yuhua (Frontiers in Immunology, 2024)
BackgroundThe treatment of vitiligo is complex, and providing guidance based on lifestyle habits is a good option that has not been summarized or analyzed.ObjectiveTo elucidate the relationship between vitiligo and lifestyle factors.MethodsFour databases (PubMed, Embase, Cochrane, and China National Knowledge Internet) were searched for articles published between 1980 and December 2022. Keywords such as smoking, drinking, exercise, diet, and sleep were used.ResultsBased on the search strategy, 875 relevant studies were retrieved, and 73 were included in this study, of which 41 studies with 8,542 patients with vitiligo were included in the meta-analysis. Vitamin C [mean difference (MD), −0.342; 95% confidence interval (CI), −1.090–0.407; p >0.05), folic acid (MD, −1.463; 95% CI, −7.133–4.208; p >0.05), and selenium (MD, 0.350; 95% CI, −0.687–1.387; p >0.05) levels did not differ between the groups. Vitamin E (MD, −1.408; 95% CI, −2.611–−0.206; p <0.05), vitamin B12 (MD, −0.951; 95% CI, −1.672–−0.275; p <0.05), copper (MD, −0.719; 95% CI, −1.185–−0.252, p <0.005), and zinc (MD, −0.642; 95% CI, −0.731–−0.554; p <0.001) levels were lower in the vitiligo group than in the control group. The serum iron level of the vitiligo group was significantly higher than that of the control group (MD, 1.181; 95% CI, 0.390–1.972; p <0.005). Finally, more participants in the vitiligo group smoked and drank alcohol than those in the control group.LimitationsMost studies are from Eastern countries; thus, extrapolating these results to Western populations is questionable. The significant heterogeneity may be attributed to the different stages, types, duration, center settings, population registries, etc., which seriously impair the validity of the results.ConclusionsPatients with vitiligo should reduce smoking and alcohol consumption and take appropriate vitamin E, B12, copper, and zinc supplements. However, vitamin C, vitamin D, selenium, iron, and folic acid supplements are unnecessary. Moreover, they should consider sun protection and avoid permanent hair dye use. Patients with vitiligo may experience sleep disturbances and sexual dysfunction, and these patients should seek help from a specialist if necessary.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#recordDetails, identifier CRD42023480757.